Beyond Dietary Fatty Acids as Energy Source: A Point of View for the Prevention and Management of Type 2 Diabetes - Varela, Lourdes M.; Ortega, Almudena; Lopez, Sergio; Bermudez, Beatriz; Abia, Rocio; Muriana, Francisco J.G. (IntechOpen, 2011)
None